Pigmentary nevi on face have unique patterns and implications: The concept of Blaschko's lines for pigmentary nevi - Nilendu Sarma (Wolters Kluwer Medknow Publications, 2012)
Background: Nevi are proposed to reflect the mosaicism and thus generally follow the different archetypal patterns of mosaicism. Blaschko's lines are the most common pattern of mosaicism. There have been many attempts to elucidate the Blaschko's lines on face from the distributional patterns of different nevi, but studies that evaluated exclusively pigmentary nevi are sparse. Aims: This study attempted to evaluate the patterns followed by different pigmentary nevi on face and utilized this to elucidate the pattern of embryological pigmentation on face. Materials and Methods: Spatial parameters like shape, orientation, and distribution patterns of different flat pigmentary nevi on face were analyzed and graphically drawn on human facial diagram. This was compared with existing facial Blaschko's lines. All cases of palpable pigmented nevi like congenital and giant melanocytic nevi and nevus spilus were excluded. Results: A total of 68 cases of pigmentary nevi on face (male-39, female-29) were examined. The shape and distribution lines were found to have a close similarity with Blaschko's lines on face with distinct differences. Conclusions: The concept of facial embryonic pigmentary 'segment', 'unit' and existence of separate Blaschko's lines for facial pigmentary nevi is conceived. Some insight into the pathogenesis of Blaschko's lines is also proposed in this study.